2020
DOI: 10.1200/jco.2020.38.15_suppl.579
|View full text |Cite
|
Sign up to set email alerts
|

Establishing analytical and clinical similarity between HD201 and herceptin.

Abstract: 579 Background: Trastuzumab, an approved prescription drug by EMA and FDA under the name Herceptin has become the key treatment in patients with HER2−positive breast cancer. HD201, developed by Prestige Biopharma Pte Ltd is a biosimilar candidate to Herceptin. The biosimilarity of HD201 was established based on systematic stepwise comparisons between HD201 and reference product, Herceptin. In order to confirm clinical similarity of HD201 to Trastuzumab, two clinical studies were undertaken. Methods: First, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…After applying our exclusion criteria, we identified 42 studies, and 11 were excluded after final review, leaving 31 studies involving 12 310 patients for detailed analysis (Figure 1; eTable 1 in the Supplement). Twenty-one studies presented an overall low risk of bias, 2 had a high risk of bias, and for 2 trials, the risk of bias was unclear (eTable 2 in the Supplement). All trials were preregistered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After applying our exclusion criteria, we identified 42 studies, and 11 were excluded after final review, leaving 31 studies involving 12 310 patients for detailed analysis (Figure 1; eTable 1 in the Supplement). Twenty-one studies presented an overall low risk of bias, 2 had a high risk of bias, and for 2 trials, the risk of bias was unclear (eTable 2 in the Supplement). All trials were preregistered.…”
Section: Resultsmentioning
confidence: 99%
“…All but 5 were double-blinded. Eleven studies compared brand-name bevacizumab with a biosimilar, 9 compared brand-name trastuzumab with a biosimilar, and 11 compared brand-name rituximab with a biosimilar …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, nine brands of trastuzumab (BCD-022, ABP980, SB3, CT-P6, PF-05280014, HD201, TrastuRel, MYL-1401O, HLX02) were examined (Table 1). All studies on trastuzumab were conducted with either paclitaxel [11][12][13][14][21][22][23][24][25][26][27][28][29][30] or docetaxel (with 5 fluorouracil epirubicin cyclophosphamide (FEC) [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] or carboplatin, 46,47 or as monotherapy [15][16][17]48,49 ) or 'taxane' [50][51][52][53][54] (Table 2). One study, by Apsangikar et al, was conducted independently, 21 while all other studies were funded by the innovator company or by an unknown source.…”
Section: Included Studiesmentioning
confidence: 99%
“…Forty-one studies reporting on RCTs were identified and included in the analysis, with 34 studies reporting efficacy outcomes (Table 1). Among all included studies, seven reported on ABP 980, 12,[22][23][24][28][29][30] two on BCD-022, 11,27 seven on CT-P6, [31][32][33][34][43][44][45] two on HD201, 14,50 five on HLX02, [15][16][17]48,49 four on MYL-1401O, [51][52][53][54] five on PF-05280014, 13,25,26,46,47 eight on SB3, [35][36][37][38][39][40][41][42] and one on Trasturel. 21 All studies contained data in treatment-na€ ıve patients, and seven studies 12,[22][23][24][28][29]…”
Section: Study Outcomes: Efficacymentioning
confidence: 99%